The functional analysis of rare genetic variants in a familial neurodegenerative spectrum disorder - Faergeman, S (2018)
Whole genome sequencing can enable an unbiased approach to the diagnosis and to the understanding of genetic aetiology of neurodegenerative diseases, which are a clinically and genetically heterogeneous group of disorders. Two brothers, originally diagnosed with primary progressive multiple sclerosis (PPMS), displayed an atypical disease progression over a 30-year period with a clinical picture of paresis, ataxia, mental impairment and dysarthria. Late stage fasciculations, absence of sensory symptoms and a follow-up magnetic resonance imaging (MRI) scan showing severe atrophy of the cerebrum, cerebellum and brainstem, but no white matter lesions, called the original diagnosis into question. Given the familial nature and the rarity of this very similar clinical profile, we hypothesised that a rare variant could be contributing to disease. Whole genome sequencing identified three rare variants segregating with disease: a homozygous non-frameshift deletion in the fatty acid 2-hydroxylase (FA2H) gene, an X-bound non-synonymous single nucleotide variant in the adaptor protein-1 complex subunit sigma-2 (AP1S2) gene, and a homozygous frameshift deletion in the mixed lineage kinase domain-like protein (MLKL) gene. Lipidomic analysis using liquid chromatography-tandem mass spectrometry of FA2H variant-expressing cell lines demonstrated no detrimental impact of the deletion in FA2H on protein function. Bioinformatic and computational structural analysis suggested the variant in AP1S2 to be benign. In contrast, the frameshift deletion in MLKL prevents expression of MLKL protein as demonstrated in patient-derived primary cells. The absence of MLKL was shown ex vivo to cause complete deficiency in necroptosis, a recently identified form of programmed cell death that is involved in a spectrum of neurodegenerative diseases. This thesis provides the first clinical case report implicating MLKL and necroptosis deficiency in a neurodegenerative spectrum disorder. The results suggest that current strategies to pursue MLKL inhibition for human therapy should be approached with caution.